Desenvolvimento farmacotécnico e validação analítica de comprimidos revestidos gastrorresistentes a partir do extrato padronizado de Harpagophytum procumbens DC - Lopes, Andrey Pereira [UNIFESP] (2017)
The project aimed to develop a traditional herbal medicine from the dry extract, standardized in harpagoside, from the secondary roots of the plant species Harpagophytum procumbens DC. (Pedaliaceae), popularly known as "devil's claw". The tablets were developed from the dry extract of Harpagophytum procumbens DC. and produced by direct compression. Subsequently, they were coated with the appropriate gastro-resistant dispersion. Accelerated and long-term stability studies have been performed to define the period of use and validity. Gastro-resistant coated tablets, obtained from the dried extract of Harpagophytum procumbens DC., were standardized in harpagoside, and the analytical methodology was validated.